Analisis Kinerja Usaha Jasa Olahraga Gorontalo Dengan Pendekatan Balanced Scorecard - Karunia Rahman; Syarwani Canon; Niswatin Niswatin (Al-Buhuts, 2025)
This study aims to evaluate the performance of the TS Futsal sports service business in Gorontalo using the Balanced Scorecard approach. The methodology used in this study was to distribute questionnaires to 95 customers and 4 employees which were carried out from February to September 2024. The results of the study showed that the financial performance of TS Futsal was in good condition with an average Net Profit Margin (NPM) of around 83.75%. From a customer perspective, the level of satisfaction showed positive results, especially in terms of service and ease of ordering. The internal business perspective shows that technological innovation has improved operational efficiency, although there is still a need for improvement in terms of teamwork. From a learning and growth perspective, employees feel involved in decision making, but communication between management and employees still needs to be improved. Overall, the implementation of the Balanced Scorecard provides a comprehensive picture of TS Futsal's performance and can be a strong foundation for future strategic planning. This study is expected to be a reference for other service businesses in improving performance and competitiveness.